EFFECT OF FINANCIAL LITERACY, RISK ATTITUDE AND SAVING MOTIVES TO DISPOSITION BIAS ON MUTUAL FUNDS INVESTORS - Jennifer Saputra; Dewi Astuti; Dewi Pertiwi (Finance and Investment Program, School of Business and Management - Petra Christian University, 2021)
Investment is significant to prepare human needs in the future. To make investment decisions, investors will try to make their decisions as rationally as possible. However, one cannot deny that some irrational factors or biases also influence investment decision-making. This study examines financial literacy, risk attitude, and saving motives on disposition bias of mutual fund investors. The sample used is mutual fund investors, and the respondents themselves make decisions to sell or buy mutual funds. The total of respondents is 116 respondents. The regression method used in this study is binary logistic regression using SPSS software. This study found that financial literacy and risk attitude has a significant effect on disposition bias. Meanwhile, the variable saving motives have no considerable impact on disposition bias.